2022
DOI: 10.1177/15910199221106036
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatile tinnitus due to stenosis of the supraclinoid segment of the internal carotid artery: Management with a low-profile self-expanding stent

Abstract: Atherosclerotic stenosis of the internal carotid artery is a rare cause of pulsatile tinnitus. Stenosis responsible for tinnitus is usually located in the petrous segment of the vessel or, even more uncommonly, in the extracranial segment. However, to the best of our knowledge, a stenosis of the intradural supraclinoid segment of the internal carotid had never been reported as a source of pulsatile tinnitus. We describe the case of a man with a history of previous ischaemic stroke and invalidating pulsatile ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…This observation is aligned with previous reports, which have indicated that ICA pathology (especially the petrous segment, because the closest nest to the inner auditory bones can manifest as pulsatile tinnitus) is further substantiated by the improvement following vascular interventions [ 19 ]. The existing academic discourse acknowledges instances of tinnitus arising from stenoses in the supraclinoid segment of the internal carotid artery, albeit less frequently reported [ 20 ]. In the literature, tinnitus associated with ICA stenosis is often attributed to turbulent flow across a localized narrowing, which generates a perceptible sound [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…This observation is aligned with previous reports, which have indicated that ICA pathology (especially the petrous segment, because the closest nest to the inner auditory bones can manifest as pulsatile tinnitus) is further substantiated by the improvement following vascular interventions [ 19 ]. The existing academic discourse acknowledges instances of tinnitus arising from stenoses in the supraclinoid segment of the internal carotid artery, albeit less frequently reported [ 20 ]. In the literature, tinnitus associated with ICA stenosis is often attributed to turbulent flow across a localized narrowing, which generates a perceptible sound [ 21 ].…”
Section: Discussionmentioning
confidence: 99%